Resilience in victims of stalking and obsessional relational intrusion - Blazey, Faye (2021)
Introduction: Stalking and obsessional relational intrusion (ORI) victimisation research has largely focused on negative effects, consistent with a legal requirement for stalking victims to experience fear, alarm or distress. This thesis explored victim resilience.